Can physical activity levels and relationships with energy expenditure change the clinical aspects of sarcopenia and perceptions of falls among elderly women? Observational cross-sectional study - Kemp, Vitório Luís; Piber, Leonardo de Souza; Ribeiro, Ana Paula (São Paulo Medical Journal, 2021)
BACKGROUND: Physical activity (PA) is an effective strategy for managing sarcopenia in the elderly, but few studies have addressed PA levels regarding age-related changes. OBJECTIVE: To ascertain the effects of elderly women’s PA levels on sarcopenia, physical performance, handgrip strength and perception of the risk of falling, and their relationship with energy expenditure. DESIGN AND SETTING: Observational cross-sectional study conducted in the southern region of the city of São Paulo, Brazil. METHODS: Forty-seven elderly women were evaluated and divided into three groups: low PA (n = 13); moderate PA (n = 16); and high PA (n = 18). Their PA levels were investigated through the International Physical Activity Questionnaire (IPAQ); sarcopenia index, through dual-energy radiological absorptiometry; physical performance through the Timed Up & Go test; handgrip strength, using a digital dynamometer; and perception of the risk of falling, through the Fall Risk Awareness Questionnaire. RESULTS: High PA level indicated higher skeletal muscle mass index, physical performance and IPAQ score, compared with low and moderate PA levels. Multiple linear regression analysis showed that higher IPAQ energy expenditure at high and moderate PA levels was a good predictor of higher physical performance and increased perception of the risk of falling. CONCLUSION: Elderly women classified as having high PA level showed improvements in sarcopenia, handgrip strength, physical performance and perception of the risk of falling. The IPAQ energy expenditure of the elderly women with high and moderate PA levels was a good predictor of physical performance and improved perception of the risk of falling.